NILAI TASAWUF DALAM AL-QURAN DAN HADIS RESTORASI PEMIKIRAN DAKWAH - Armyn Hasibuan (IAIN Padangsidimpuan, 2017)
Restoration of thoughts about Sufism this is due to the widespreadskepticism in the presence of a different dogma in some Sufi circles. Therestoration is to resurrect something hidden. Evoking the meaning between thelines of a verse or Hadith aimed at getting the contents of the actual content, thereis meaning behind the express is often more interesting and motivating people topractice.Surah al A'raaf ayat 172-173 describes the creed that inform whence arefirst to all the human beings that do not forget the promise of the Godhead. Manyverses that affirm faith and explain whence are, globally the life in the world andin the hereafter. His teachings should be animates all the twists of the life of everyMuslim. The texts of the other worship explained that the Almighty God whocreated man and Earth even provided their tools, in the hands of her Royal life anddeath it is two phases were created as a means of displaying human behavior,work, or his devotion to the good and the ugly.Based on verses and Hadith Hadith that was taken over the restoration ofthe values of Sufism can be reinforcing the soul of unity whereby the assessmentof fetal spirit her baby there life and giving of panca inderadan sense. Therefore,in the science of Sufism is not just a natural phenomenon seen make it rememberberzikir to God the Creator but rather look at the phenomenon of nature itselfpresents to celebrate or berzikir with metaphorical language to God the creator.